2016
DOI: 10.1177/096739111602400601
|View full text |Cite
|
Sign up to set email alerts
|

Clay/Polyethylene Composites with Enhanced Barrier Properties for Seed Storage

Abstract: The utilization of clays to enhance the water vapour barrier properties of polyethylene requires knowledge about factors associated with the constituents themselves. Hence, this paper presents combinations of two types of polyethylene and five different clays. Morphological, mechanical and thermal properties related to the water vapour permeability of clay/polyethylene composites were investigated. Although no evidence of clay exfoliation was observed according to morphological and spectral results, it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…DSC analysis was carried out to measure the crystallinity degree of the polyethylene matrix, and the results are illustrated in Figure . Our previous work pointed out an increase in crystallinity upon the addition of ME into high density polyethylene . Unlike our previous findings, ME/LDPE shows 1.5 % lower crystallinity than LDPE, thus suggesting a rather poor nucleating effect of ME on the LDPE matrix.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…DSC analysis was carried out to measure the crystallinity degree of the polyethylene matrix, and the results are illustrated in Figure . Our previous work pointed out an increase in crystallinity upon the addition of ME into high density polyethylene . Unlike our previous findings, ME/LDPE shows 1.5 % lower crystallinity than LDPE, thus suggesting a rather poor nucleating effect of ME on the LDPE matrix.…”
Section: Resultsmentioning
confidence: 67%
“…27 % by adding ME(t), ME(d), or MAE. Overall, the enhanced barrier properties of fluorohectorite/LDPE composites can be only ascribed to the tortuous pathway for gas diffusion, instead of increased crystallinity as mentioned previously . Moreover, the highest degree of crystallinity of ME/LDPE/MAPE can be explained by the fact that interfacial compatibilization promoted the contact between ME and polyethylene, consequently strengthening the nucleating effect of ME on the LDPE matrix.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Previous studies on the combination of nanoclays with polymers reported the reasonable enhancement of water vapor and gas barrier attributes of polymers. [25,26] The field of clay nanocomposite was observed to be fervently pursued due to the opportunity of concurrent improvement in thermal, barrier, and mechanical properties by using the conventional melt blending technique. [25] The acquired mechanical, thermal, and morphological properties of nanocomposites provided the evidence of linkage of barrier attributes with clay aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, the highly desirable exfoliation and dispersion are especially challenging and very difficult to obtain due to the poor compatibility between the particles and the polyolefinbased polymer matrix. [19][20][21] In the work of Picard et al, 20 the clay dispersion and barrier properties of different high-density polyethylene (HDPE)-based nanocomposites containing MMTs with different types of organomodification and a compatibilizer polymer were analyzed. Results indicate that in the composites without the compatibilizer agent, the permeability coefficients (for different gases such as H 2 , He, O 2 , and CO 2 ) were higher than in the neat HDPE.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of a well-exfoliated morphology higher reductions of the gas permeability could not be obtained. The effect of different factors associated with the constituents of polyethylene/clays composites on the water vapor barrier properties was analyzed by Hu et al 21 They found that the enhanced water vapor barrier properties were linked to clay aspect ratio, composites interface, polyethylene crystallinity, and storage conditions. This improvement in the gas barrier properties of the polymer composites make them very important in packaging and protective applications, such as food industry, pharmaceuticals, and electronic devices.…”
Section: Introductionmentioning
confidence: 99%